Grand International Meeting on Spain and Culture (leaflet) (1937)
039-0067-001 ROYAL ALBERT HALL (Manager: CHARLES B. COCHRAN) Grand International Meeting on SPAIN AND CULTURE THURSDAY, JUNE 24, at 8 p.m. Doors open 7.15 Speakers: PICASSO HEINRICH MANN PROFESSOR LANGEVIN PROFESSOR CONSTABLE In the chair: THE DUCHESS OF ATHOLL, M.P., D.B.E. Tickets from: Julius Lipton, National Joint Committee For Spanish Relief 53 Marsham St., S.W.1 Telephone: Victoria 2168 Prices: 2/6, 2/-. 1/-. 6d. Balcony and Gallery free MESSAGES BROADCAST DIRECT TO THE MEETING FROM PAUL ROBESON in Moscow, PABLO CASALS in Bucharest and Speakers from Madrid Supported by : Professor Lascelles Abercrombie, Vanessa Bell, Professor P.M.S. Blackett, F.R.S., Professor W.E. Le Gros Clark, F.R.S., Sean O'Casey, Havelock Ellis, E.M. Forster, Gwen Ffrangçon-Davies, Duncan Grant, Professor J.B.S. Haldane, F.R.S., E.X. Kapp, Professor John MacMurray, H.W. Nevinson, The Hon. Harold Nicolson, M.P., Philip Noel-Baker, M.P., John Robertson Scott (Editor of the "Countryman"), Professor Charles Singer, Dame Sybil Thorndike, Professor J.B. Trend, H.G. Wells, Virginia Woolf. IN AID OF THE BASQUE REFUGEE CHILDREN UNDER THE AUSPICES OF THE NATIONAL JOINT COMMITTEE FOR SPANISH RELIEF Printed by the VICTORIA HOUSE PTG. CO. LTD. (T.U. all Depts.), 55 and 57 Drury Lane, London, W.C.2 292/946/39/67